The Role of Teachers in Building Gender Identity and Equality in Integrated Islamic Kindergartens in Banda Aceh - Ramadhani, Leony Novita (Sinthop: Media Kajian Pendidikan, Agama, Sosial dan Budaya, 2025)
This study aims to examine the construction of gender identity and roles, as well as the practice of socializing gender equality values by teachers in three Integrated Islamic Kindergartens (TKIT) in Banda Aceh. Employing a qualitative case study approach, data were collected through participatory observation and in-depth interviews with teachers at TKIT Al-Fatih, Permata Sunnah, and Khalifah 3. The findings reveal that teachers adopt thematic and contextual approaches to introduce gender identity and encourage cross-gender interactions through play, discussions, and exemplary behavior. The pedagogical practices reflect transformative efforts toward inclusive education responsive to equality. However, subtle biases in communication patterns indicate the need to strengthen gender literacy among educators. These findings confirm that Islamic educational institutions can serve as strategic spaces to instill gender equality values through reflective, critical, and contextual approaches.